Ocean liming can help achieve the Paris climate target - Jessica Strefler; Katarzyna Kowalczyk; Verena Hofbauer; Tabea Dorndorf; Lavinia Baumstark (Environmental Research Letters)
To stabilize global mean temperature and stay below critical thresholds, deep emission reductions have to be complemented with carbon dioxide removal. A broad portfolio of options is necessary to enable sufficient potential and mitigate sustainability concerns. So far, integrated assessment models have almost exclusively considered options on land. In this study, we show that ocean liming can make a substantial contribution to achieving ambitious climate mitigation targets. Due to the expected time needed for scale-up, the deployment potential in the first half of the century is limited, such that ocean liming can hardly reduce peak temperature. However, in the second half of the century, substantial deployment may be economically competitive. In addition, the availability of ocean liming reduces the dependence on other carbon removal options, and specifically on bioenergy. This could reduce the pressure on land and improve the sustainability of ambitious climate mitigation scenarios. However, impacts on the ocean ecosystems are still poorly understood and need to be clarified before deployment. In light of the remaining uncertainties and global and regional limitations, we suggest to limit the maximum global deployment of ocean liming in integrated assessment models to 5 GtCO _2 /yr carbon uptake.